Comparison of Serum Folic Acid Level in Oral Lichen Planus Patients and Healthy Subjects - AR Mirzaie; M Hashemi Shahzadeh; M Barzegari; A Azizi (Islamic Azad University, 2018)
Background and aim: Oral lichen planus (OLP) is a chronic mucocutaneous inflammatory disease. Although the etiology of this disease is unknown, some factors including stress, antioxidant deficiency, and folic acid deficiency have been claimed to have a role in its incidence. The purpose of this study was to assess and compare the serum folic acid level in OLP patients and healthy subjects. Materials and methods: in this case-control study, 52 OLP patients (36 females and 16 males) were selected as the case group, and 48 healthy individuals (36 females and 12 males) were assigned to the control group. The serum folic acid level was measured in the two groups. Data were analyzed using T-test with the level of significance set at 0.05. Results: the mean and standard deviation (SD) of serum folic acid level was equal to 8.74±4.11 ng/ml in the case group and 9.12±3.5 ng/ml in the control group with no statistically significant difference (P=0.12). Conclusion: The results of the present study indicated that the serum folic acid level in OLP patients did not have a significant difference with that in healthy subjects.